Patient - friendly information giving in HIV counselling through the use of metaphor - Haladin, Nur’ain Balqis (Penerbit UTM Press, 2022)
HIV counselling is a method of communication between patients and certified HIV nurse counsellors to discuss and help patients deal with HIV-related issues. Despite the training received by these nurses, communicating HIV-related issues remains a difficult task in Malaysia. Due to lack of research examining information giving in HIV counselling in Malaysia, this study investigated both the challenges and the strategies in providing information to HIV patients. Twenty-four audio recordings of actual HIV counselling sessions were gathered and six focus group discussions with HIV nurse counsellors from three government hospitals in Malaysia were recorded. The discourse analysis of revealed a prominent use of metaphors as part of information giving strategies to overcome the challenges faced by HIV nurse counsellors when communicating with HIV patients. The metaphors were embedded in HIV nurse counsellors’ information giving to HIV patients and their spouse/family as a way to represent some medical jargons pertaining to HIV. Since the HIV patients came from different educational background, it would be much easier for them to understand HIV-related information giving through the use of metaphors. Therefore, the acknowledgement and integration of metaphors can be an amazingly valuable tool for HIV nurse counsellors especially in managing the communication challenges during HIV counselling. It is hoped that the findings provided in this study will serve as a basis for integrating metaphors into counselling practices.